2023
DOI: 10.1021/acsmaterialslett.3c00626
|View full text |Cite
|
Sign up to set email alerts
|

A Diboron-Based Thermally Activated Delayed Fluorescent Material for Versatile Applications of Organic Light-Emitting Diodes

Chia-Min Hsieh,
Yi-Kuan Chen,
Jian Lei
et al.

Abstract: Thermally activated delayed fluorescence (TADF) organic light-emitting diodes (OLEDs) have attracted public attention due to their high external quantum efficiency (EQE) and implication in future display technology. Despite their improved efficiency, TADFbased OLEDs still suffer from serious efficiency roll-off and short operational lifetimes. Herein, a diboron-based molecule, PhCzDBA, is designed and its device exhibits a maximum EQE (EQE max ) of 33.8% and only slight roll-off (EQE max of 31.5% at 1000 cd m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…In the last two decades, organic light-emitting diodes (OLEDs) have attracted great attentions owing to the use of the triplet excited-available emitters. As one promising type of these emitters, thermally activated delayed fluorescent (TADF) emitters are capable of pushing 75% triplet excitons to emit via the reverse intersystem crossing (RISC) process, and theoretically the 100% internal quantum efficiency (IQE) can be achieved. However, the ultralong delayed lifetime usually leads to the serious fluorescence quenching in aggregate states. As a result, the luminescent efficiency is sharply compromised in OLEDs under high current density, which is called efficiency roll-off. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the last two decades, organic light-emitting diodes (OLEDs) have attracted great attentions owing to the use of the triplet excited-available emitters. As one promising type of these emitters, thermally activated delayed fluorescent (TADF) emitters are capable of pushing 75% triplet excitons to emit via the reverse intersystem crossing (RISC) process, and theoretically the 100% internal quantum efficiency (IQE) can be achieved. However, the ultralong delayed lifetime usually leads to the serious fluorescence quenching in aggregate states. As a result, the luminescent efficiency is sharply compromised in OLEDs under high current density, which is called efficiency roll-off. , …”
mentioning
confidence: 99%
“…As a result, the luminescent efficiency is sharply compromised in OLEDs under high current density, which is called efficiency roll-off. 9,10 To address the above challenge, many approaches, such as selecting suitable functional layers in a device and modifying the molecular structures of emitters, have been reported. Among all these methods, from the perspective of the device, doping the TADF emitters in an appropriate hosts is one of the most effective method to reduce triplet exciton density.…”
mentioning
confidence: 99%
“…Thus, it is essential to improve the device structure and materials to increase the outcoupling efficiency. Some recent studies have shown that QD-LEDs and PeLEDs can achieve an EQE above 25% without using any out-coupling enhancement method [20][21][22][23][24][25] .…”
mentioning
confidence: 99%
“…Photoluminescent (PL) materials have wide applications in bioimaging, light-emitting diodes, anti-counterfeiting and sensing. 1,2 Persistent exploration towards this direction has led to the emergence of encouraging new materials, among which carbon dots (CDs) have received increasing attention due to their ease of preparation and tunable luminescence. 3 Compared to traditional chromophores, CDs lack a defined molecular structure, which leads to a more complicated PL mechanism.…”
mentioning
confidence: 99%